The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3846/16111699.2016.1148628
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Macroeconomic Indices on European Private Labels

Abstract: In this study, we have analysed the impact and evolution of some of the most important macroeconomic indices on market share and value of private labels. The originality of this paper is the linkage of macroeconomic variables of European countries and the evolution of private labels in these nations. This relationship may show the development of commercial distribution with regard to macroeconomic indices. A sample of 13 European countries and a period of 14 years have been collected, including data of private… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…In this sense, given the importance of the private label, it would be of great importance for retailers and/or other organizations to know if macroeconomic indicators can be a determining factor for the implementation of private label in various countries, thus, in this study we have followed previous studies [32] to determine the main macro indicators with respect to private label, namely GDP, Unemployment, Average Wage, Per Capita Debt, and Consumer Price Index. Urban Concentration was not used in this study, because of its low impact.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…In this sense, given the importance of the private label, it would be of great importance for retailers and/or other organizations to know if macroeconomic indicators can be a determining factor for the implementation of private label in various countries, thus, in this study we have followed previous studies [32] to determine the main macro indicators with respect to private label, namely GDP, Unemployment, Average Wage, Per Capita Debt, and Consumer Price Index. Urban Concentration was not used in this study, because of its low impact.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…This imbalance in employment causes changes in the individuals who are in this situation, both on a mental level and on a purchasing behavior level [39]. Therefore, several studies have taken unemployment into account when studying private labels [32,35] and several have had this indicator as one of the main macroeconomic indicators for the economic study of a country [40,41]. For this reason, it will be one of the macroeconomic indicators used in this study for the analysis of the private label.…”
Section: Unemploymentmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in the review of the literature we find different works that have demonstrated the implications of macroeconomic indices with private brands (Gil Cordero et al 2016;Stanton and Meloche 2011;Dubé et al 2018;Wyma et al 2014), but given the importance of private brands in Europe (Verhoef et al 2002) and in the USA (Verhoef et al 2002). With few researchers following this line of research (Kaswengi et al 2020;Latorre et al 2020;Minimol and Nair 2020).…”
Section: Introductionmentioning
confidence: 99%
“…With few researchers following this line of research (Kaswengi et al 2020;Latorre et al 2020;Minimol and Nair 2020). It is important to know whether the research demonstrated by Gil-Cordero (Gil Cordero et al 2016) is equally widespread in the USA and to establish the basis for organizations operating in both territories. The choice of the U.S. compared to Europe was made because they are two continents that differ more culturally in the 6 sections studied by the tool Hofstede Insights (Hofstede Insights 2020); in this sense, we will study if a culture opposite to Europe behaves the same way in reference to private label.…”
Section: Introductionmentioning
confidence: 99%